An optimal multiscale approach to interpret gravity data using successive decomposition of the Bouguer anomaly - ARFAOUI, Mohamed; INOUBLI, Mohamed Hedi; AMIRI, Adnen (Contributions to Geophysics and Geodesy, 2018)
A multiscale interpretive approach is presented to identify multiscale discontinuities and sources boundaries, and to obtain comprehensive pseudo-section density images of 2D structures at depth. This interpretive approach is based on the total horizontal gradient and apparent density operator applied to the gravity anomalies of pseudo-depth slices derived from the successive decomposition of the Bouguer anomaly. This approach is applied to gravity data from the northwestern part of Tunisia, it provides the fault system repartition at different depths and describes the density distribution within the basins and trough. Thus, the NW–SE and NE–SW faults are the deepest whereas the N–S and E–W faults are relatively superficial. The density pseudo-sections reveal the vertical continuity of salt Triassic outcrops of Jebel Debadib as well as a diapiric model,the presence of a Triassic salt dome in the Kalaa El Khasba through and dense series under the Miopliocene and Quaternary deposits of the Mejarda basin.